Characterizing the SBS polymer degradation within high content polymer modified asphalt using ATR-FTIR. (10th February 2020) - Yan, Chuanqi; Huang, Weidong; Ma, Jianmin; Xu, Jing; Lv, Quan; Lin, Peng
Highlights: A total of 18 field and laboratory aging conditions were assessed. Much more sulfoxide is observed in field aged samples than laboratory aged ones. R3.2% reduces with increasing testing temp while phase angle remains stable. Polymer degradation causes more influence on the binder phase angle. Asphalt oxidation causes more influence on the binder stiffness. Abstract: High Content Polymer Modified Asphalt (HCPMA) can notably improve asphalt pavement performance. But Styrene–Butadiene–Styrene (SBS) polymer is sensitive to aging and its degradation significantly detriments the HCPMA engineering property, and thus it is of great importance to monitor the SBS degradation during the HCPMA aging. In this study, Attenuated Total Reflection Fourier Transform infrared spectroscopy (ATR-FTIR) was applied to characterize the SBS polymer degradation. A total of 17 lab/field aging conditions were considered. Infrared indices derived from spectrum semi-quantitatively analysis were correlated with binder rheology properties (G*, δ, Jnr3.2, R3.2). Results show that due to polymer degradation, HCMPA binder with a higher aging level generally has a higher stiffness with less elasticity. Moreover, HCPMA is vulnerable to high-temperature short-term aging and shows more resistance to the long-term aging at intermediate temperature. The applicability of standard laboratory bituminous aging, namely Rolling Thin Film Oven Aging (RTFO) and Pressure Vessel Aging (PAV), for HCPMA appears to be questionable. On one side, both RTFOT and PAV yield a much smaller aging degree than the actual HCPMA field aging. On the other side, significant sulfoxide generations are observed for field aged binders while RTFOT and PAV aging hardly generate any sulfoxide. Additionally, phase angle and R3.2% as two binder elasticity measurements were compared and they show different behaviors with increasing testing temperatures due to their different testing strains.